SPONTANEITY ELEMENTS FOUND IN SPOKEN DISCOURSE OF UNIVERSITY STUDENTS - Dina Novita Wijayanti; Atik Rokhayani (Universitas Muria Kudus, 2022)
Speaking English is useful to share information to other people around the world. To communicate appropriately, the students can fulfill the features of spontaneity. In fact, the students of Psychology Department of Muria Kudus University find difficulty to achieve the ideal situation. They do not know how to respond to the speaker spontaneously. To fill the empty space, the participants can apply spontaneity elements. The study is intended to analyze and explain the types of spontaneity elements found in the spoken discourse of university students and the university students’ understanding of spoken discourse. The design of the study used is discourse analysis. The participants were 16 students who did job interviews in pairs for 10 minutes. To collect the data is by using documentation. The findings showed that the types of spontaneity elements found in spoken discourse of university students are 176 occurrences consist of 45 repetitions (25.6%), 121 filled pauses (68.7%), 1 backtracking (0.6%), 9 incomplete utterances (5.1%). The students often use filled pauses to maintain the speaking consistency and seldom to use backchannels because they seldom to restatement the previous utterance while the students’ understanding of spoken discourse is low. It occurs because 3 elements of spontaneity are less than 50%, while 1 element is more than 50%. The students are actively speaking English only in the class. So, it is suggested for the students to speak English in daily life because by practicing to speak English, it can increase progress.